Among dardy, szpady, szpontony and sztylety: Italianisms in the Polish nomenclature of bladed and pole weapons - Palmarini, Luca (Kwartalnik Neofilologiczny, 2026)
The study examines Italianisms attested in the Polish language within the domain of terminology related to bladed and pole weapons. Following a historical overview of the development of this type of weapon in the Italian Peninsula, a typological classification is proposed, which serves as the analytical framework for examining the lexical borrowings under consideration. The terms analysed are investigated using Polish corpora from the sixteenth to eighteenth centuries, as well as Italian and French corpora and etymological dictionaries. The results highlight a significant Italian contribution, reflecting the circulation in Poland of military models and techniques of Italian origin, and the receptiveness of the Polish context to innovations from Western Europe, with processes of linguistic mediation also occurring via French and German.